Maximizing pearl millet (Pennisetum glaucum) productivity and profitability using site specific nutrient management strategy - SINGH, SANDEEP; PANDEY, MANOJ; SINGH, VINAY (The Indian Journal of Agricultural Sciences, 2019)
Field experiment was conducted during kharif 2014 and 2015 at farmers’ field at Panwari village of Agra district (Uttar Pradesh) to study the effect of site specific nutrient management (SSNM) on productivity, profitability and uptake of nutrients by pearl millet [Pennisetum glaucum (L) R.Br.]. The experiment was laid out in randomized block design with 10 treatments and three replications. Results, pooled over two years, indicated that the SSNM led to significant increase in grain and stover yield of pearl millet as compared to the state recommended NPK fertilizers and farmers’ practice. SSNM increased the grain yield of pearl millet by 30.6 and 42.2% over state recommended NPK fertilizers and farmer practice, respectively. The maximum net profits of Rupees 45209/ha with a B:C ratio of 2.71 was obtained from pearl millet under SSNM. The minimum net profits (Rupees 29818/ha) and B:C ratio (2.53) were recorded under farmer practice. Omission of P, K, S and Zn nutrients caused grain yield reductions by 22.4% , 24.0% , 7.4% and 7.0% over SSNM, respectively. The uptake of N, P, K, S and Zn by pearl millet grain and stover in SSNM was higher than that of the farmer’s practice. The protein content and protein yield also improved with various treatments over farmers’ practice and the maximum values for both were recorded under SSNM. The fertility status of soil increased with various treatments and the maximum values of organic carbon (4.0 g/kg), available N (204.5 kg/ha), P (16 kg/ha), K (144 kg/ha), S (22.4 kg/ha) and Zn (0.61 mg/kg) were recorded with 120 kg N+60 kg P2O5 + 90 kg K2O+ 20 kg S + 4 kg Zn/ha over other treatments. Omission of S and Zn caused a reduction in available S and Zn status over their initial values.